Non-Necrotizing Acute Dermohypodermal Infections in Cirrhotic Patients Being Evaluated for Liver Transplantation - Santos, Vitoria Caroline Moreno dos; Cretelli, Olívia S.; Valsechi, Linoel Curado; Meirelles, Matheus B.; Marcatto, Gustavo; Silva-Isepon, Lincoln B. da; Itimura, Priscilla; Silva-Fucuta, Patrícia da; Silva, Renato Ferreira da (Brazilian Journal of Transplantation, 2025)
Introduction: Infections in cirrhotic patients have a significant impact on morbidity and mortality, but little is known about acute non-necrotizing dermohypodermal infections (erysipelas and infectious cellulitis) in this population. The high mortality in this group also represents a loss of opportunity for liver transplantation, which could be a potential solution for these patients. Objectives: This study aims to describe the clinical characteristics, evolution, and outcomes of cirrhotic patients with acute non-necrotizing dermohypodermal infections under evaluation for liver transplant. Methods: A retrospective study was conducted on patients hospitalized with cirrhosis and dermohypodermal infections from 2010 to 2012. Results: Among 983 patients with liver cirrhosis, leading to 2,046 consultations for decompensated cirrhosis, dermohypodermal infections were identified in 65 (7%) cases. The mean age was 58 years (± 10), with 82% male. Cellulitis predominantly affected the lower limbs (70%), followed by the trunk (21%) and upper limbs (9%). Alcoholic liver disease was the primary etiology (56%), followed by alcohol and hepatitis C (17%), isolated hepatitis C (13%), non-alcoholic steatohepatitis (9%), and hepatitis B (3%). Based on the Child-Pugh score, 8% were classified as class A, 46% as class B, and 46% as class C. The average model for end-stage liver disease (MELD) score was 20 (± 8). Commonly associated infections included urinary tract infection (54%), pneumonia (25%), and spontaneous bacterial peritonitis (21%). Prescribed antibiotics were clindamycin (71%), cephalosporins (40%), oxacillin (18%), penicillin (11%), vancomycin (11%), quinolones (4.5%), and other antibiotics (15.3%). Sepsis occurred in 14% of cases, and the mortality rate was 18.5% (n=12). Among the deceased patients, 67% (n=8) had concomitant infections with cellulitis. Factors significantly associated with mortality were concomitant infections (69 vs. 31%, p = 0.02) and elevated C-reactive protein levels (6 vs. 3 mg/dL, p = 0.03). Conclusion: This study highlights the high hospital mortality rate among cirrhotic patients with acute non-necrotizing dermohypodermal infections, especially when concomitant infections are present. The high mortality not only reflects the severity of the condition but also represents a loss of opportunity for potentially life-saving interventions, such as liver transplantation. Further research is needed to improve the management of cirrhotic patients with dermohypodermal infections.